ПРОИЗВОДСТВО ХЛЕБОБУЛОЧНЫХ ИЗДЕЛИЙ АНТИДИАБЕТИЧЕСКОГО ДЕЙСТВИЯ (World Science, 2020)
The article discusses the ways to solve the problems of low levels of active biological substances in the bakery product, with medicinal properties. In the process of the preparation of buns, the optimal dosages of the additives were calculated in order to determine an acceptable ratio of vegetable raw materials components and expand the range of bakery products with therapeutic and prophylactic effects. The article proposes new recipe for making buns with the addition of herbal additives such as stevia and licorice root. In addition, the study was conducted on the influence of licorice root and stevia additives on the rheological properties of the dough and the quality of the finished product. As a result, high-quality buns with the necessary consumer properties were obtained.